ORGANIC PRODUCTS MARKET AND CONSUMERS’ ATTITUDES TOWARDS ORGANIC PRODUCTS - Vapa Tankosić, Jelena; Carić, Biljana (International Journal of Economic Practice and Policy, 2024)
The development of the market for organic products has been recorded in many countries. The organic products market segment in the specific environment of the Republic of Serbia is gradually developing. In times of the COVID-19 pandemic, the interest in organic products increased. Expressed health concern has been perceived as one of the most important reasons for buying organic food. Therefore, the aim of this paper is to investigate the development of the organic products market and consumer attitudes towards organic products, as well as the factors that influence their behaviour, which should be taken into account when creating an adequate promotional strategy for this specific market.